Epidemic characteristics and transmission risk prediction of brucellosis in Xi'an city, Northwest China - Zhao, Chenxi; Liu, Kun; Jiang, Chenghao; Wei, Xiao; Song, Shuxuan; Wu, Xubin; Wen, Xiaohui; Fu, Ting; Shen, Li; Shao, Zhongjun; Li, Qian (Frontiers in Public Health, 2022)
Human brucellosis (HB) has re-emerged in China since the mid-1990s, and exhibited an apparent geographic expansion shifted from the traditional livestock regions to the inland areas of China. It is often neglected in nontraditional epidemic areas, posing a serious threat to public health in big cities. We carried out a retrospective epidemiological study in Xi’an, the largest city in northwestern China. It utilizes long-term surveillance data on HB during 2008–2021 and investigation data during 2014–2021. A total of 1989 HB cases were reported in Xi’an, consisting of 505 local cases, i.e., those located in Xi'an and 1,484 nonlocal cases, i.e., those located in other cities. Significantly epidemiological heterogeneity was observed between them, mainly owing to differences in the gender, occupation, diagnostic delays, and reporting institutions. Serological investigations suggested that 59 people and 1,822 animals (sheep, cattle, and cows) tested positive for brucellosis from 2014-2021, with the annual average seroprevalence rates were 1.38% and 1.54%, respectively. The annual animal seroprevalence rate was positively correlated with the annual incidence of nonlocal HB cases. Multivariate boosted regression tree models revealed that gross domestic product, population density, length of township roads, number of farms, and nighttime lights substantially contributed to the spatial distribution of local HB. Approximately 7.84 million people inhabited the potential infection risk zones in Xi’an. Our study highlights the reemergence of HB in nonepidemic areas and provides a baseline for large and medium-sized cities to identify regions, where prevention and control efforts should be prioritized in the future.